Aromatic hydrocarbons multiple nuclei (PAHs) in falling dust in the province of Basra - Al-ddin, Shaima; Aziz, Nayef (Iraqi Journal of Science, 2024)
The study included determine the concentration of hydrocarbons aromatic multiple nuclei PAHs in dust falling in the province of Basra, for the period from October 2011 to September 2012 included five stations on the province of Basra (Zubayr and bab Al-Zubair and Qarmat -Ali and Abu Alkaseb), and has been collecting study samples per month and estimated the amount of fallout and various pollutants associated with him. The exercise was conducted to draw vehicles hydrocarbon and examined device Gas chromatography and extracted data for compounds aromatic multiple nuclei PAHs were analyzed statistically observed discriminate compound B (b) F + B (k) F and Chrysene highest rates compared compounds aromatic other stations of the study, and found an increase in concentration of compound Benz (a) anthraceneas reached 6.904 Mcgm / kg Dry weight and composite Benzo (a) pyrene concentration 6.170 Mcgm / kg in the station Bab Al-Zubair, and sacrificed the study results on site in concentrations PAHs have been recorded lower values rates concentrations vehicles aromatic PAHs in plant Abu- Al kaseb compared with other study stations.